Food Systems Transformation in Nepal: Commitments and Challenges in Boosting Nature-Positive Food Production - Suwal, Rojee; Dahal, Kishor Chandra; Dangol, Dharma Raj; Panta, Hari Krishna; Adhikari, Jagnnath (Nepalese Journal of Agricultural Sciences, 2025)
Nepal stands at a pivotal moment in its development trajectory as it prepares to graduate from least developed country status by 2026. Despite this milestone, food insecurity, malnutrition, and unsustainable agricultural practices persist, exacerbated by climate change, demographic shifts, and global geopolitical trade dynamics. The current food systems fail to deliver sufficient, nutritious, and safe food for a growing population without damaging natural resources and the environment. In response, Nepal developed the 2021 Food Systems Transformation Strategy, aligning with global pathways to build sustainable, resilient, and equitable food systems. Translating these commitments into tangible action requires alignment with policy, planning, and fiscal investment. However, achieving Action Track 3, which focuses on boosting nature-positive food production at scale, remains a significant challenge due to entrenched policy practices, low public investment, knowledge and capacity gaps, and limited implementation of sustainable agriculture initiatives. The concept of food systems is not new to Nepal; however, there is limited literature examining the evolving shifts and dynamics of food systems and their transformation pathways toward achieving triple outcomes, beyond food security and economic growth. The main objectives of this paper are to identify barriers to implementing nature-positive food systems at the scale in Nepal and to offer insights and lessons that should be prioritized to effectively advance the goals outlined in Nepal’s Food Systems Transformation Strategy 2021. This paper analyzes Nepal’s policy landscape, agricultural performance, and gaps in sustainable agriculture implementation to examine their alignment with nature-positive food systems goals. Drawing on national and international experiences, it identifies systemic barriers, including policy incoherence, insufficient local capacity, limited research and innovation, and lack of empirical evidence, that hinder the adoption and scaling of sustainable practices. A "one-size-fits-all" approach to transform the systems is inadequate for Nepal’s diverse agroecological zones, marked by significant provincial variation and increased demographic and socio-economic changes. The paper advocates for a transformative mindset, governance, investment, and multi-stakeholder coordination shifts to foster nature-positive food systems tailored to Nepal’s diverse context. Key actions include enhancing local capacities, reorienting subsidies, improving governance and monitoring systems, and strengthening private sector engagement. Ultimately, a systems-oriented and context-specific approach is essential to accelerate the transition toward environmentally sustainable and inclusive food systems in Nepal.